(untitled) (Bulletin of criminological association of Ukraine, 2025)
The article is devoted to the criminological analysis of specific corruption schemes among military personnel that emerged after the start of Russia’s full- scale armed aggression against Ukraine. Nine types of corruption schemes are identified, described and explained. It is established that they remain stable, institutionalized forms of criminal activity regarding the exploitation of budgetary resources or actual opportunities related to service. The task of increasing the effectiveness of countering their reproduction is actualized, which requires the implementation of new systemic approaches that will provide for additional measures of independent control over the movement of budgetary funds, minimizing the human factor in this process, and high-quality operational support for the activities of the Armed Forces of Ukraine.